Implementasi Sistem Informasi Laman Sinta Dalam Meningkatkan Manajemen Publikasi Ilmiah: Studi Kasus di LPPM UNS - Widyantoro Yuliatmojo; Arius Ayu Saputri (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This research provides a theoretical examination of the implementation of the Science and Technology Index (SINTA) Information System to enhance the management of scholarly publications at the Research and Community Service Institute (LPPM) of Sebelas Maret University (UNS). SINTA, serving as a platform indexing and presenting information on scholarly publications, is the focal point of this study with the aim of improving the efficiency and effectiveness of scholarly publication management within the academic environment of LPPM UNS.The study commences by offering a theoretical overview of SINTA, encompassing its roles and primary functions in providing information on scholarly publications. Subsequently, the fundamental concepts of scholarly publication management are analyzed in detail, involving processes such as article submission, metadata management, and researcher performance monitoring at the institutional level.The significance of implementing SINTA in enhancing research visibility, real-time monitoring of researcher performance, and facilitating easy information access becomes a primary focus in identifying the benefits of this implementation. Additionally, case studies and examples of successful implementations at LPPM UNS will provide a concrete illustration of how SINTA can be effectively applied in the context of scholarly publication management.However, the study also includes an analysis of challenges and obstacles that may be encountered during the implementation process, including data security, accurate information availability, and integration with other existing information systems within the institution.Through this study, specific recommendations are expected to be generated for LPPM UNS to enhance the implementation of SINTA as a primary tool in scholarly publication management. The conclusions drawn from this study aim to provide deeper insights into the role of the Science and Technology Index Information System in improving the effectiveness and quality of scholarly publications at LPPM UNS.